Organizational Commitment, Information Asymmetry, and the Nature of Conscientiousness as Moderating the Relationship of Budget Participation to Budgetary Slack - Putri, Yuthika Rani; Solikhah, Badingatus (Universitas Negeri Semarang, 2018)
This study aims to analyze whether organizational commitment, information asymmetry and the nature of conscientiousness can moderate the effect of budgetary participation on budgetary slack. The population of this research is 31 OPD Semarang City. The minimum number of samples that can be taken based on the slovin formula is 24 OPD. Sampling technique used random sampling. The number of respondents are 120 echelon three and four officials. The data in the study was the primary data taken through the spread of questionnaires. Data were analyzed using descriptive analysis and Moderate Regression Analyze with SPSS 21 program. Based on the result of the research, it showed that budget participation had a positive effect on budgetary slack. Organizational commitment and the nature of conscientiousness variables were proven to moderate the effect of participation on budgetary slack. Meanwhile, the information asymmetry variable could not be a moderating variable. The conclusion of this research is the higher the budget participation, the higher the incidence of budgetary slack so that hypothesis 1 is rejected. Organizational commitment and high conscientiousness of budget participation affect the budgetary slack but its effect to weaken.